Modeling the Vegetation Dynamics of Northern Shrubs and Mosses in the ORCHIDEE Land Surface Model - Arsène Druel; Philippe Ciais; Gerhard Krinner; Philippe Peylin (Journal of Advances in Modeling Earth Systems, 2019)
Abstract Parameterizations of plant competition processes involving shrubs, mosses, grasses, and trees were introduced with the recently implemented shrubs and mosses plant functional types in the ORCHIDEE dynamic global vegetation model in order to improve the representation of high latitude vegetation dynamics. Competition is based on light capture for growth, net primary productivity, and survival to cold‐induced mortality during winter. Trees are assumed to outcompete shrubs and grasses for light, and shrubs outcompete grasses. Shrubs are modeled to have a higher survival than trees to extremely cold winters because of thermic protection by snow. The fractional coverage of each plant type is based on their respective net primary productivity and winter mortality of trees and shrubs. Gridded simulations were carried out for the historical period and the 21st century following the RCP4.5 and 8.5 scenarios. We evaluate the simulated present‐day vegetation with an observation‐based distribution map and literature data of boreal shrubs. The simulation produces a realistic present‐day boreal vegetation distribution, with shrubs, mosses north of trees and grasses. Nevertheless, the model underestimated local shrub expansion compared to observations from selected sites in the Arctic during the last 30 years suggesting missing processes (nutrients and microscale effects). The RCP4.5 and RCP8.5 projections show a substantial decrease of bare soil, an increase in tree and moss cover and an increase of shrub net primary productivity. Finally, the impact of new vegetation types and associated processes is discussed in the context of climate feedbacks.